Penyusunan Project Planning Pembangunan Tempat Pemrosesan Akhir Kabupaten Jombang - Yuni Rokhmawati; Sitti Safiatus Riskijah; Moch Khamim (Publikasi Indonesia, 2022)
The Jombang TPA Development Project is a project owned by the Ministry of PUPR, carried out by PT. Adhi Karya (Persero), Tbk. with a landfill capacity of 5 hectares, not only that PT. Adhi Karya (Persero), built supporting buildings such as leachate water installations, management buildings and employee buildings. In 2020 there was an outbreak of Covid-19 which resulted in a setback in the implementation of construction projects. Project planning is an alternative in planning project realization due to the COVID-19 outbreak in terms of implementation methods, quality planning, safety, health and environment, costs to be incurred, and scheduling. Based on the results of this writing, the site layout, traffic management, implementation strategy using the zoning system are obtained, with an implementation time of 446 days, the quality plan refers to occupational health and safety specifications and controls referring to OHSAS 18001: 2007, the planned implementation budget is Rp. 127,446,097,744,- including 10% VAT.